“Saber que vem da terra"”: múltiplos olhares sobre as práticas do raizeiros(as) no setor central e nas feiras na cidade de Anápolis-GO entre os anos de 2022 a 2024 - (:unkn) unknown (Universidade Estadual de Goiás, 2024)
The research is in the field of Cultural Geography, a science that represents one of the most dynamic areas in the field of geography, since it studies cultural products, their codes and norms, analyzing their variations and transformations through spaces and places. With this, in this context, the importance of conserving the Savanna is verified, because it is where most medicinal plants come from. Its general objective is: To understand the knowledge and popular practices of herbalists in the central sector and in the markets in Anápolis-GO; The specific objectives: To identify the origin and succession of the knowledge and popular practices of the herbalists in the central sector and in the markets in Anápolis - GO; To point out the strategies for the insertion of popular knowledge from the perspective of the central sector and in the markets in Anápolis - GO; Analyze the means by which the population accesses knowledge about the use of medicinal plants. It is known that from the knowledge about medicinal plants, legislation was created where it establishes standards for the manufacture of herbal edicines. In this context, the problem question raised was: What are the strategies for the permanence and continuity of the knowledge of the Herbalists in the city of Anápolis in the State of Goiás? The hypothesis raised was that the resistance and continuity of the knowledge of the herbalists of the city of Anápolis are due to popular commerce and the markets held in the city's neighborhoods. The methodology used was field research, through observations, interviews, photographic records.
"Knowing that it cmes from the earth": multiple perspectives on the practices of rootworkers in the central area and markets in the city of Anápolis-GO between 2002 and 2024
Keywords: Geografia cultural – Cerrado goiano; Fitoterápicos – Cerrado – Goiás(Estado); Plantas medicinais - Raizeiros – Cerrado – Anápolis(GO); Herbal Medicines - Cerrado goiano; Medicinal Plants - Cerrado goiano; GEOGRAFIA::GEOGRAFIA HUMANA; BOTANICA::FITOGEOGRAFIA